Capital Structure Theory in the Transport Sector: Evidence from Visegrad Group - Jaroslav Mazanec (Mathematics, 2023)
Capital structure plays an important role in corporate finance, especially in the period of restrictive monetary policy in many developed countries. This paper aims to estimate the debt ratio based on five selected financial indicators: tangibility, return on assets, size of total assets, current ratio, and size of total sales using multiple linear regression for four countries, such as the Czech Republic, Hungary, Poland, and Slovakia, as well as the V4 region. The total sample consists of 3828 small- and medium-sized enterprises from the transport sector in the Central European area. These data are drawn from Amadeus by Bureau van Dijk from 2019. The results show that three of the five variables are statistically significant in all models. These findings indicate that transport companies prefer the pecking order theory. We find that the increase in tangibility, return on assets, as well as current ratio, reduce the debt ratio. The outputs provide new theoretical and empirical knowledge regarding transport companies in V4.